(untitled) (Journal of Advanced Research in Social Sciences, 2024)
Competence describes pedagogical processes involving teachers, students, contents, methodologies, and skills for new social and academic grounds. It encompasses gender equality-based awareness to enhance students’ critical thinking as active educators. This longitudinal study describes an interdisciplinary project to raise awareness of gender equality at secondary school, provides a space for teachers and students to address gender-based violence in a flexible student-based and response-based PBL methodology while self-sustained engagement and motivation heightens more complex cognitive development and competence. Results conclude that intrinsic motivation levels increase dramatically when students’ awareness regarding social impact is accomplished, schools benefit from students’ inclusion in planning and decision-making processes, and gender awareness is enhanced as they become active social educators. Most importantly, students’ self-motivated and sustained increase of meta-awareness and metacognitive strategies relate to active decision-making in the context of gender-based violence and social and academic education.